2021
DOI: 10.3389/fpsyt.2021.650674
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence and Correlates of Schizophrenia and Other Psychotic Disorders in Singapore

Abstract: Introduction: The current study aimed to establish the lifetime prevalence of schizophrenia and other psychotic disorders, its sociodemographic correlates and association with physical disorders using data from the Singapore Mental Health Study (SMHS 2016).Methods: A two-phase design comprising population-level screening of psychotic symptoms using the World Health Organization Composite International Diagnostic Interview version 3.0 psychosis screen followed by clinical reappraisal based on the Diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Participants who endorsed positive psychotic symptoms on the screener questionnaire were further assessed for lifetime schizophrenia and other psychotic disorders (i.e. brief psychotic disorder, schizophreniform disorder, schizoaffective disorder, delusional disorder, substance-induced psychotic disorder, and psychotic disorder not otherwise specified) on the SCID-1 by experienced clinicians ( Subramaniam et al, 2021 ). Accordingly, participants who were diagnosed with any of these mood and schizophrenia spectrum disorders were categorized into the severe mental disorders group; a binary (yes/no) outcome variable was formulated for severe mental disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Participants who endorsed positive psychotic symptoms on the screener questionnaire were further assessed for lifetime schizophrenia and other psychotic disorders (i.e. brief psychotic disorder, schizophreniform disorder, schizoaffective disorder, delusional disorder, substance-induced psychotic disorder, and psychotic disorder not otherwise specified) on the SCID-1 by experienced clinicians ( Subramaniam et al, 2021 ). Accordingly, participants who were diagnosed with any of these mood and schizophrenia spectrum disorders were categorized into the severe mental disorders group; a binary (yes/no) outcome variable was formulated for severe mental disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Schizophrenia is a chronic and severe mental illness affecting 20 million people worldwide ( 5 ). A recent study conducted in Singapore reported that ~2.3% of Singapore's general adult population are affected by schizophrenia and related psychoses in their lifetime ( 6 ). People with schizophrenia are commonly perceived as unpredictable and dangerous ( 7 ), with fears of being injured by an individual with severe mental illness being fairly common in the general public ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Singapore, the prevalence of schizophrenia spectrum and other psychotic disorders was 2.3% in the adult population, with an early age of onset (23.1 years) and low treatment gap [80.4% sought treatment, ( 23 )]. The Early Psychosis Intervention Programme (EPIP), a multidisciplinary nationwide program aims to diagnose and manage psychosis at an early stage to improve treatment outcomes and long-term prognosis ( 24 ).…”
Section: Introductionmentioning
confidence: 99%